If B, equals, minus, m, plus, 1, minus, 9, m, squaredB=−m+1−9m

2
and A, equals, m, plus, 9, commaA=m+9, find an expression that equals 2, B, minus, 2, A2B−2A in standard form.

1 answer

To find an expression that equals 2B - 2A in standard form, we need to substitute the values for B and A into the expression and simplify it.

Given that B = -m + 1 - 9m^2 and A = m + 9, we can substitute these values into the expression: 2B - 2A.

2B - 2A = 2(-m + 1 - 9m^2) - 2(m + 9)

Simplifying this expression step by step:

= -2m + 2 - 18m^2 - 2m - 18
= -20m - 18m^2 - 16

Therefore, the expression that equals 2B - 2A in standard form is -18m^2 - 20m - 16.
Similar Questions
  1. If B, equals, 3, x, minus, x, squaredB=3x−x2 and C, equals, x, minus, 8, minus, 8, x, squared, commaC=x−8−8x 2 , find an
    1. answers icon 1 answer
  2. If B, equals, 1, minus, 6, w, squaredB=1−6w2 and A, equals, 1, plus, w, commaA=1+w, find an expression that equals 2, B,
    1. answers icon 1 answer
    1. answers icon 12 answers
  3. Transform the linear equation 4x−8y=24 to slope-intercept form.(1 point)Responses 4x−8y−24=0 4 x minus 8 y minus 24 equals
    1. answers icon 1 answer
more similar questions